Современная энциклопедия для девочек от 6 до 12 лет - Скиба Тамара Викторовна (Владис, 2019)
Экземпляры: ф.18 (20220325) / Инвентарный номер: 4010 / Цена: / Сис.шифр: 92 / Авт.знак: С 56 / ГРНТИ: 00.39 / ББК: 92я2